WOMEN IN ANTHROPOLOGICAL FILM (ЕтноАнтропоЗум/EthnoAnthropoZoom, 2015)
Visual anthropology has never been fully incorporated into the anthropological mainstream. For a long period, anthropological films have been considered only as an objective recording of reality to be used in further analysis and then stored in film archives – as it is also considered to be an audio-visual aid in the teaching process. My field experience supports the ever-dominant thesis that visual anthropology, the same as written texts, is a narrative means to impart anthropological knowledge. In this case, the focus is on the anthropology of women – a topic, which in social sciences and in films was ”invisible“ until the 1970.
Keywords: visual anthropology; film; women; traditional culture